On the Prospects of Digitalization of Justice - Stepanov, Oleg; Pechegin, Denis; Diakonova, Maria (Legal Issues in the Digital Age, 2021)
The article considers the problem of digitalization of judicial activities in the Russian Federation and abroad. Given the fact that in the modern world elements of digital (electronic) justice are gaining widespread adoption, the article presents an analysis of its fundamental principles and distinguishes between electronic methods of ensuring procedural activity and digitalization of justice as an independent direction of transformation of public relations at the present stage. As a demonstration of the implementation of the first direction, the article presents the experience of foreign countries, Russian legislative approaches and currently being developed legislative initiatives in terms of improving the interaction of participants in the procedure through the use of information technologies. The authors come to the conclusion that the implemented approaches and proposed amendments are intended only to modernize the form of administration of justice with new opportunities to carry out the same actions (identification of persons participating in the case, notification, participation in the court session, etc.) without changing the essential characteristics of the proceedings. The second direction, related to electronic (digital) justice, is highlighted from the point of view of the prospects and risks of using artificial intelligence technologies to make legally significant decisions on the merits. At the same time, the authors argue that the digitalization of justice requires the development and implementation of the category of justice in machine-readable law, as well as special security measures of both technological and legal nature.